2012
DOI: 10.5251/ajsir.2012.3.3.115.121
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution kinetics and mechanisms of reaction of Udi clay in nitric acid solution

Abstract: The dissolution kinetics and mechanisms of reaction of Udi clay in nitric acid have been studied. Leaching temperature, acid concentration, particle size, solid-to-liquid ratio, and stirring speed were selected as process parameters. It was observed that the dissolution rate increased with decreasing particle size and solid-to-liquid ratio and increased with stirring speed, acid concentration, and leaching temperature. (S/L) -0.3104 (w) 0.2709 exp (-2621/T) t. The activation energy of the process was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…A nucleation model was applied and concluded that the reaction with respect to aluminum was of the first order and had an activation energy of 108.68 kJ/mol. Ajemba and Onukwuli [12] investigated the dissolution kinetics and mechanisms of reaction of Udi clay in a nitric acid solution (excess above 90%). The clay was calcinated at 700 ºC and showed extractable alumina concentrations of 26.5% with a high concentration of Fe 2 O 3 (18.45%) and the presence of interferents such as K 2 O, SO 3 , MgO and others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A nucleation model was applied and concluded that the reaction with respect to aluminum was of the first order and had an activation energy of 108.68 kJ/mol. Ajemba and Onukwuli [12] investigated the dissolution kinetics and mechanisms of reaction of Udi clay in a nitric acid solution (excess above 90%). The clay was calcinated at 700 ºC and showed extractable alumina concentrations of 26.5% with a high concentration of Fe 2 O 3 (18.45%) and the presence of interferents such as K 2 O, SO 3 , MgO and others.…”
Section: Resultsmentioning
confidence: 99%
“…Kaolin is a possible alternative to bauxite because it contains high alumina concentrations and is abundant in the Amazon region. The aluminum production process using kaolin can also produce silica with high specific area [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.0 (-1.000) 1.5 (0.000) 2.0 (+1.000) In order to establish the kinetic parameters and rate-controlling step for the leaching of lead from 'Enugu Coal' in nitric acid solution, the experimental data were fitted to the kinetic models. Such plots are quite extensively used in kinetic studies [9]. The kinetic relationships are expressed in terms of the fraction of reacted particle X, with time.…”
Section: Kinetics Of Leaching Processmentioning
confidence: 99%
“…Some researchers used acid and alkali treatment for surface properties modifi cation of the selected minerals as reported earlier 10, 11 . However, to evaluate which methods of activation show excellent results, an ellaborative characterization of these porous materials regarding their pore size, surface area, porosity and pore size distribution, morphology and thermal properties are required to select and optimize the performance of porous and hierarchically structured & ordered materials for both direct and indirect use in many industrial applications 16- 19 . In this work we will study and evaluate the effectiveness of the intercalation procedure for original as well as variously intercalated pre-baked clay samples in turn of their morphological characteristic.…”
Section: -9mentioning
confidence: 99%